Lithium ion battery

By using a specific combination of positive electrode materials and electrolytes in lithium-ion batteries, the lithium ion transmission speed is adjusted, and the problems of lithium dendrites formation and battery stability are solved, and high-temperature storage performance and safety performance are improved.

CN119133570APending Publication Date: 2024-12-13ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411277230.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Lithium-ion batteries have problems such as lithium dendrites forming, reduced battery stability, large safety hazards and reduced capacity at high temperatures, especially in high-rate charging and discharging and long-term high-temperature storage.

Method used

The core body and surface structure of the positive electrode material are adopted. The core body contains LiaMOb main material and B ions, and the surface layer contains A ions. A variety of nitrile compounds are added to the electrolyte. The combination of nitrile functional groups and the transmission speed of lithium ions is adjusted and Embed speed to form a semiconductor diode structure to improve material stability and interface stability.

Benefits of technology

It significantly improves the high-temperature storage and safety performance of lithium-ion batteries, reduces the risk of lithium dendrites, and improves the charging efficiency and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005040589260000101
    Figure BDA0005040589260000101
  • Figure BDA0005040589260000111
    Figure BDA0005040589260000111
  • Figure BDA0005040589260000112
    Figure BDA0005040589260000112
Patent Text Reader

Abstract

The invention provides a lithium ion battery which comprises a positive plate and electrolyte, and a positive material of the positive plate comprises a core body and a surface layer located on the surface of the core body; wherein the core body comprises a main material with a chemical general formula of LiaMOb, the electrolyte comprises two or more dinitrile compounds and a polynitrile compound, and the number of the dinitrile compounds is two or more. Compared with the prior art, the positive electrode material adopted by the invention can effectively improve the interface stability of the positive electrode, and the added nitrile compound can effectively complex transition metal ions on the surface of the positive electrode, so that the side reaction of the positive electrode and an electrolyte is further reduced, and the cycling stability of the battery at high temperature can be fully improved; and the effects of improving the charging capability and improving the high-temperature storage can also be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of secondary batteries, and in particular to a lithium ion battery. Background Art

[0002] Lithium-ion batteries play a vital role in many applications, especially in mobile communications, electric vehicles and large-scale energy storage systems. However, with the advancement of technology and the continuous growth of market demand, the performance requirements for lithium-ion batteries are also increasing, especially in terms of high-rate charge and discharge performance. When charging at high rates at room temperature, lithium-ion batteries face a series of technical challenges.

[0003] First, the speed at which lithium ions migrate between electrodes becomes a limiting factor. When the battery is charged at a high rate, the rapid migration of lithium ions leads to a significant increase in the lithium ion concentration gradient between the electrodes. Especially at the negative electrode, the limitation of the lithium ion embedding speed leads to the formation of lithium dendrites. Lithium dendrites are a microstructure of metallic lithium, and their growth not only reduces the cycle stability and service life of the battery, but also greatly increases the risk of short circuit and thermal runaway, seriously threatening the safety of the battery.

[0004] During long-term high-temperature storage, the electrolyte can react with the positive electrode at high temperature and high voltage, destroying the structure of the positive electrode material. At the same time, the byproducts such as carbon dioxide can cause the battery volume to expand, and water can react with the negative electrode. The stability of the lithium battery will be sharply reduced, posing a great safety hazard. At the same time, when the solid products of the side reaction will accumulate on the surface of the positive and negative electrodes, the internal resistance of the lithium battery will increase, resulting in a decrease in the capacity of the lithium battery, thereby shortening the service life of the lithium battery.

[0005] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention

[0006] One of the purposes of the present invention is to provide a lithium ion battery to improve the storage performance of the current lithium ion battery at high temperature in view of the deficiencies of the prior art.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A lithium-ion battery, comprising a positive electrode sheet and an electrolyte, wherein the positive electrode material of the positive electrode sheet comprises a core body and a surface layer located on the surface of the core body; wherein the core body comprises a chemical formula of Li a MO bThe main material is a, a has a value range of 1 to 3, b has a value range of 1 to 3, M is at least one of transition metal ions, and the valence state of the M ion is +X; the surface layer contains A ions, and the valence state of the A ions is +Y; the core contains B ions, and the valence state of the B ions is +Z; wherein both A and B are at least one of the main group or subgroup elements of IA to IVA; and X, Y, and Z satisfy the relationship: 1<Z<X≤Y;

[0009] The electrolyte includes dinitrile compounds and polynitrile compounds, the dinitrile compounds are two or more, and the content of each of the dinitrile compounds does not exceed 2% of the total mass of the electrolyte, the number of nitrile groups in the polynitrile compounds is ≥3, the polynitrile compounds are at least one, and the content of each of the polynitrile compounds does not exceed 3% of the total mass of the electrolyte; the total content of the dinitrile compounds is E%, and the total content of the polynitrile compounds is F%, wherein F≤E≤3F.

[0010] Preferably, the dinitrile compound includes at least two of succinonitrile, adiponitrile, glutaronitrile, 2-methyleneglutaronitrile, pimelonitrile, suberonitrile, and 2-fluoroadiponitrile; the polynitrile compound includes at least one of 1,2,3-tris(2-cyano)propane, 1,3,6-hexanetricarboxylic acid nitrile, 1,3,5-pentanetricarboxylic acid nitrile, 1,2,2,3-tetracyanopropane, and 1,2,4,5-tetracyanobenzene.

[0011] A variety of nitriles are used in combination, and the nitrile functional group and the Co in the positive electrode material 3+ The binding energy is relatively negative, so it is easier to accumulate on the positive electrode surface. At the same time, the nitrile functional group coordinates with the high-valent transition metal atoms on the positive electrode surface, making the positive electrode material more stable at high temperatures, thereby reducing the side reactions between the positive electrode and the electrolyte and significantly improving the high-temperature storage performance of the battery.

[0012] Preferably, based on the mass of the main material, the mass content of the M ions is ≥ 10%.

[0013] Preferably, the weight proportion of the A ions in the surface layer is ≥200ppm; and / or, the interval extending 1μm from the surface of the core body toward its center is defined as the inner layer, and the weight proportion of the B ions in the inner layer is ≥200ppm. If the content of A ions in the surface layer is too low, the effect of reducing the lithium ion transmission speed cannot be achieved. Similarly, if the content of B ions in the core body is too low, the effect of increasing the lithium ion transmission speed cannot be achieved. By adopting the content parameters defined above in the present invention, the technical effect of simultaneously improving the electrode lithium precipitation and low-temperature discharge capacity can be achieved.

[0014] On the surface of the positive electrode material, the valence state of the A ion needs to be ≥ that of the M ion to achieve the effect of reducing the lithium ion transmission speed, and the effect is more obvious when the weight ratio of the A ion in the surface layer is ≥200ppm, and there is no effect when the content is lower. Inside the positive electrode, the valence state of the B ion needs to be ≤ that of the M ion to achieve the effect of promoting the lithium ion transmission speed, and the effect is more obvious when the weight ratio of the B ion in the inner layer is ≥200ppm. Lithium ions are inhibited by A ions when they are transmitted to the surface, and promoted by B ions when they are transmitted to the interior. The simultaneous presence of the two ions can achieve the effect of regulating the lithium ion extraction and embedding speed, thereby improving the room temperature high-rate charging performance and low-temperature discharge capacity of lithium batteries.

[0015] In some embodiments, the surface layer may also contain B ions appropriately, but in order to ensure that the surface layer inhibits the lithium ion transmission rate, the content of B ions needs to be controlled. Based on the weight ratio of A ions in the surface layer being ≥200ppm, the weight ratio of B ions in the surface layer needs to be controlled at 0-100ppm. If it exceeds this range, it will seriously affect the lithium ion transmission inhibition effect of the surface layer. Similarly, the core body may also contain A ions appropriately, but in order to ensure that the core body enhances the lithium ion transmission rate, the content of A ions needs to be controlled. Based on the weight ratio of B ions in the inner layer being ≥200ppm, the weight ratio of A ions in the inner layer needs to be controlled at 0-100ppm. If it exceeds this range, it will seriously affect the lithium ion transmission promotion effect of the core body.

[0016] Preferably, the method for preparing the positive electrode active material comprises the following steps:

[0017] S1, mixing the main material preparation raw materials including the lithium source and the M element precursor, and then dispersing them in an organic solvent, adding the B element precursor for premixing, and vacuum drying the mixture;

[0018] S2, dividing the mixture in step S1 into two groups, a and b, and then sintering them respectively to obtain product a and product b;

[0019] S3, crushing the product a and the product b prepared in S2 respectively to obtain large particles of product a and small particles of product b;

[0020] S4, mixing the large particles and the small particles obtained in S3 in a mass ratio of (7-9):(1-3), adding the A element precursor, and stirring and mixing;

[0021] S5. The mixture obtained in S4 is subjected to secondary sintering, crushing, and cooling to obtain the positive electrode material.

[0022] Preferably, in step S1, the premixing speed is 200-400 r / min, and the premixing time is 4-8 h; the vacuum drying temperature is 60-100° C., and the drying time is 10-15 h.

[0023] Preferably, in step S2, the primary sintering temperature is 800-1200°C, the primary sintering of the mixture of group a adopts a two-stage sintering method and the sintering time is 12-14 hours, and the primary sintering time of the mixture of group b is 5.5-7.5 hours.

[0024] Preferably, the two-stage sintering method includes: first continuously heating the temperature to D1°C at a heating rate of V1°C / min, then sintering at D1°C±50°C for t1 time, then continuously heating the temperature to D2°C at a heating rate of V2°C / min, then sintering at D2°C±50°C for t2 time, and finally annealing at a cooling rate of V3°C / min, wherein V1>V2, V2=V3, D1<D2, and t1=t2.

[0025] Preferably, the stirring and mixing speed in step S4 is 1000-1400 rpm, and the stirring time is 5-8 hours.

[0026] Preferably, in step S3, the crushed product a is large particles of 5 to 50 μm, and the crushed product b is small particles of 0.5 to 10 μm.

[0027] Preferably, in step S5, the secondary sintering temperature is 600-800° C., and the sintering time is 8-12 hours.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: the lithium-ion battery provided by the present invention has significant advantages in improving safety performance and charging efficiency by adjusting the electrolyte components and using a positive electrode sheet in combination. The positive electrode material in the positive electrode sheet adopts AB ions with different valences distributed radially to form an NP structure similar to a semiconductor diode, which has better structural stability, thermal stability and electrochemical performance. The surface layer of the positive electrode material can effectively reduce the thermal expansion caused by temperature changes during the deintercalation and extraction of lithium from the positive electrode material, and effectively improve the interfacial stability of the positive electrode material, while also playing a good role in alleviating the decomposition of the electrolyte and the corrosion of the positive electrode material; the combination of multiple nitriles in the electrolyte provided by the present invention can complex the transition metal ions on the surface of the positive electrode, and by combining multiple different nitriles in a specified proportion, the transition metal ions on the surface of the positive electrode can be effectively complexed, the space utilization rate is higher, the protection effect is better, and the effect of improving the charging capacity and improving high-temperature storage is achieved. DETAILED DESCRIPTION

[0029] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0030] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0031] The present invention aims to provide a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode material of the positive electrode sheet comprises a core body and a surface layer located on the surface of the core body; wherein the core body comprises a chemical formula of Li a MO b The main material is a, a has a value range of 1 to 3, b has a value range of 1 to 3, M is at least one of transition metal ions, and the valence state of the M ion is +X; the surface layer contains A ions, and the valence state of the A ions is +Y; the core contains B ions, and the valence state of the B ions is +Z; wherein both A and B are at least one of the main group or subgroup elements of IA to IVA; and X, Y, and Z satisfy the relationship: 1<Z<X≤Y;

[0032] The electrolyte includes dinitrile compounds and polynitrile compounds, the dinitrile compounds are two or more, and the content of each of the dinitrile compounds does not exceed 2% of the total mass of the electrolyte, the number of nitrile groups in the polynitrile compounds is ≥3, the polynitrile compounds are at least one, and the content of each of the polynitrile compounds does not exceed 3% of the total mass of the electrolyte; the total content of the dinitrile compounds is E%, and the total content of the polynitrile compounds is F%, wherein F≤E≤3F.

[0033] Among them, the specific value of the above a can be 1, 1.5, 2, 2.5, 3, and may include but are not limited to the values ​​listed above; the specific value of the above b can be 1, 1.5, 2, 2.5, 3, and may include but are not limited to the values ​​listed above.

[0034] The inventors found that the IA~IVA main group or subgroup element ions with different positive valence states have an electrostatic repulsive effect on lithium ions, and the higher the valence state, the greater the electrostatic repulsion. The outer layer contains high-valence A ions with greater repulsion, while the inner layer contains low-valence B ions with less repulsion. The positive electrode material particles form a structure with large surface lithium ion transmission resistance and small inner lithium ion transmission resistance. In this way, when charging, lithium ions escape from the inside of the positive electrode material particles to the outside, and need to move from the inner layer with less repulsion to the surface layer with greater repulsion. They will encounter corresponding resistance, which can reduce the upper limit of the outward transmission speed of lithium ions, thereby reducing the risk of lithium precipitation at the negative electrode. During low-temperature discharge, lithium ions are embedded inward from the surface of the positive electrode material particles, and need to move from the surface layer with greater repulsion to the inner layer with less repulsion. Their transmission speed can be improved, thereby improving the low-temperature discharge capacity of the battery.

[0035] Wherein, the dinitriles include two or more of succinonitrile, adiponitrile, glutaronitrile, 2-methyleneglutaronitrile, pimelonitrile, suberonitrile and 2-fluoroadiponitrile; the polynitriles include at least one of 1,2,3-tris(2-cyano)propane, 1,3,6-hexanetricarboxylic acid nitrile, 1,3,5-pentanetricarboxylic acid nitrile, 1,2,2,3-tetracyanopropane and 1,2,4,5-tetracyanobenzene; preferably, the dinitriles are selected from succinonitrile and adiponitrile, and the polynitriles are selected from 1,2,3-tris(2-cyano)propane.

[0036] A variety of nitriles are used in combination, and the nitrile functional group and the Co in the positive electrode material 3+ The binding energy is relatively negative, so it is easier to accumulate on the positive electrode surface. At the same time, the nitrile functional group coordinates with the high-valent transition metal atoms on the positive electrode surface, making the positive electrode material more stable at high temperatures, thereby reducing the side reactions between the positive electrode and the electrolyte and significantly improving the high-temperature storage performance of the battery.

[0037] In some embodiments, the method for preparing the positive electrode active material comprises the following steps:

[0038] S1, mixing the main material preparation raw materials including the lithium source and the M element precursor, and then dispersing them in an organic solvent, adding the B element precursor for premixing, and vacuum drying the mixture;

[0039] S2, dividing the mixture in step S1 into two groups, a and b, and then sintering them respectively to obtain product a and product b;

[0040] S3, crushing the product a and the product b prepared in S2 respectively to obtain large particles of product a and small particles of product b;

[0041] S4, mixing the large particles and the small particles obtained in S3 in a mass ratio of (7-9):(1-3), adding the A element precursor, and stirring and mixing;

[0042] S5. The mixture obtained in S4 is subjected to secondary sintering, crushing, and cooling to obtain the positive electrode material.

[0043] The positive electrode material prepared by the preparation method of the present invention has better structural stability, thermal stability and electrochemical performance. Among them, the coating material can effectively reduce the thermal expansion caused by the temperature increase during the lithium insertion and extraction process of the positive electrode material, and effectively reduce the mechanical attenuation of the coating layer, improve the interface stability of the positive electrode material, and at the same time play a good role in alleviating the decomposition of the electrolyte and the corrosion of the positive electrode material, so that the electrochemical performance of the positive electrode material under high voltage is improved.

[0044] In some embodiments, in step S1, the speed of the premix is ​​200-400 r / min, specifically 200 r / min, 210 r / min, 220 r / min, 230 r / min, 240 r / min, 250 r / min, 260 r / min, 270 r / min, 280 r / min, 290 r / min, 300 r / min, 310 r / min, 320 r / min, 330 r / min, 340 r / min, 350 r / min, 360 r / min, 370 r / min, 380 r / min min, 400r / min may include but are not limited to the values ​​listed above; the premixing time is 4-8h, specifically 4h, 5h, 6h, 7h, 8h, and may include but are not limited to the values ​​listed above; the vacuum drying temperature is 60-100℃, specifically 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, and may include but are not limited to the values ​​listed above; the drying time is 10-15h, specifically 10h, 11h, 12h, 13h, 14h, 15h, and may include but are not limited to the values ​​listed above.

[0045] In some embodiments, in step S2, the primary sintering temperature is 800-1200°C, and specifically can be 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, and can include but are not limited to the values ​​listed above. The primary sintering of the mixture of group a adopts a two-stage sintering method and the sintering time is 12-14h, and the primary sintering time of the mixture of group b is 5.5-7.5h.

[0046] Among them, the two-stage sintering method includes: first continuously heating the temperature to D1℃ at a heating rate of V1℃ / min, then sintering at D1℃±50℃ for t1 time, then continuously heating the temperature to D2℃ at a heating rate of V2℃ / min, then sintering at D2℃±50℃ for t2 time, and finally annealing at a cooling rate of V3℃ / min, wherein V1>V2, V2=V3, D1<D2, t1=t2.

[0047] In some embodiments, the stirring and mixing speed in step S4 is 1000-1400 rpm, specifically 1000 rpm, 1050 rpm, 1100 rpm, 1150 rpm, 1200 rpm, 1250 rpm, 1300 rpm, 1350 rpm, 1400 rpm, 1450 rpm, 1500 rpm, and may include but are not limited to the values ​​listed above; the stirring time is 5-8 h.

[0048] In some embodiments, in step S5, the secondary sintering temperature is 600-800°C, specifically 600°C, 650°C, 700°C, 750°C, 800°C, and may include but are not limited to the values ​​listed above; the sintering time is 8-12h, specifically 8h, 9h, 10h, 11h, 12h, and may include but are not limited to the values ​​listed above.

[0049] The present invention is calcined in steps within the above calcination temperature range, and controls from multiple aspects to ensure the radial distribution of A and B elements in the final surface layer and inner layer, effectively improving the control of the radial structure of the positive electrode of the lithium cobalt oxide positive electrode material to solve the problem of high rate charging and low temperature discharge capacity performance being difficult to balance.

[0050] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto.

[0051] Example 1

[0052] The preparation method of the positive electrode material is:

[0053] 1) Primary mixing: Li 2 CO 3 、Co 3 O 4 According to the Li:Co element stoichiometric ratio of 1.05:0.993, in order to compensate for the loss of lithium under high temperature sintering, the lithium source is measured at an excess of 5%, isopropanol is used as a dispersant, and the B element precursor is added. The solid and liquid mixtures are premixed in an oblique mixer, the premixing mechanical speed is 300r / min, and the mixing time is 6h. After premixing, the above materials are vacuum dried at 80°C overnight for 12h to volatilize the dispersant and water.

[0054] 2) Primary sintering: The premixed mixture is divided into two groups, a and b, and then transferred to a muffle furnace for sintering at 800-1200°C. Specifically, the mixture of group a is sintered in two stages: the temperature is continuously increased at a heating rate of 3°C / min for the first 3 hours, and then maintained at a temperature platform of 500-600°C for 2 hours. From the 5th to the 11th hour, the temperature is continuously increased at a heating rate of 1.5°C / min, and then maintained at a temperature platform of 1050±30°C for 2 hours. Finally, annealing is performed at a cooling rate of 1.5°C / min to obtain product a after primary sintering. The mixture of group b is sintered at 1000°C for 6 hours to obtain product b after primary sintering.

[0055] 3) Primary crushing: crush product a with a crusher at a medium crushing degree for 2 hours to obtain large particles; crush product b with a crusher at a medium crushing degree for 4 hours to obtain small particles.

[0056] 4) Secondary compounding: Mix large particles and small particles in a mass ratio of 8:2, add element A precursor, 500ppm Al 2 O 3 and 800ppm LiF (LiF acts as a coating flux), the mixture is transferred to a high-speed stirrer with a stirring speed of 1000-1400r / min and stirred for 6h.

[0057] 5) Secondary sintering: The mixture was transferred to a muffle furnace again, and the heating rate was set to 5°C / min until the temperature reached 750±30°C, and sintered for 10 hours, and then cooled at a cooling rate of 3°C / min until it cooled to room temperature to obtain a secondary sintered product.

[0058] 6) Secondary crushing: The secondary sintered product is crushed with a crusher, the crushing degree is selected to be medium, and the time is 4 hours to obtain the positive electrode material.

[0059] In this embodiment, the B element precursor is MgF 2 , A element precursor is TiO 2 .

[0060] Preparation of electrolyte: In a glove box filled with argon, the moisture content is less than 5ppm, the oxygen content is less than 5ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl propionate (EP) and propyl propionate (PP) are mixed in a mass ratio of 1:1:2:2:2 to obtain an organic solvent, and 13.7% of lithium hexafluorophosphate, 1% of the total mass of the electrolyte, and 5% of the total mass of the electrolyte. Fluorinated ethylene carbonate is added and mixed evenly, and then succinonitrile (SN), adiponitrile (ADN) and 1,2,3-tris(2-cyano)propane (TCP) are added according to the addition amounts in Table 3 to obtain an electrolyte.

[0061]

[0062] The difference between Example 2-10 and Example 1 is only the amount of nitriles added to the electrolyte, as shown in Table 3.

[0063] The rest is the same as that of Example 1 and will not be described in detail.

[0064] Comparative Examples 1-9

[0065] The difference between Comparative Examples 1-9 and Example 1 is only the amount of nitriles added to the electrolyte, as shown in Table 3.

[0066] The rest is the same as that of Example 1 and will not be described in detail.

[0067] Comparative Examples 10-15

[0068] The difference between Comparative Examples 10-15 and Example 5 is only that the positive electrode sheets are different, as shown in Table 1 and Table 3 for details.

[0069] The rest is the same as that of Example 1 and will not be described in detail.

[0070] Preparation of the battery: The positive electrode sheet made of the above positive electrode material, the negative electrode sheet made of the graphite material and the polyethylene separator are wound into a bare battery cell; the battery is packaged with an aluminum-plastic film, vacuum dried at 80°C, and the electrolyte is injected after the water content reaches the standard, and the battery is packaged. After the formation, liquid extraction, capacity separation, aging and other processes, a lithium-ion battery is prepared.

[0071] The positive electrode sheets and electrolyte formulations of the above-mentioned Examples 1 to 10 and Comparative Examples 1 to 15 were sorted out as shown in Tables 1 to 3.

[0072] Table 1

[0073]

[0074] In Table 1, “ / ” represents that no relevant element is added.

[0075] Pole piece A: No A or B element precursors are added during the preparation of the positive electrode material.

[0076] Pole piece B: No B element precursor is added to the primary mixing material during the preparation process of the positive electrode material.

[0077] Pole piece C: No A element precursor is added to the secondary mixing material during the preparation of the positive electrode material.

[0078] Pole D: Add B element precursor MgF into the primary mixing material during the preparation of the positive electrode material. 2 , add A element precursor TiO 2 .

[0079] Pole E: Add TiO to the primary compound of the positive electrode material 2 MgF is added to the secondary compound 2 .

[0080] Pole piece F: A and B element precursors are added simultaneously to the primary mixture for preparing the positive electrode material, and A and B element precursors are not added to the secondary mixture.

[0081] Pole piece G: In the primary mixture for preparing the positive electrode material, no A and B element precursors are added, and A and B element precursors are added simultaneously in the secondary mixture.

[0082] After the prepared lithium-ion battery was disassembled and cleaned, the positive electrode was cut using CP, and the cross section was tested using SEM-EDS to test the A and B element contents on the surface and inside, respectively. The B element ratio is the weight ratio of B ions in the inner layer, and the inner layer is defined as above. The A element ratio is the weight ratio of A ions in the surface layer. The results are shown in Table 2:

[0083] Table 2

[0084]

[0085] The combinations of the positive electrode and the electrolyte of the relevant embodiments are shown in Table 3 below, wherein the content of nitrile is calculated based on the total mass of the electrolyte.

[0086] Table 3

[0087]

[0088]

[0089] The electrical properties of the above-mentioned Examples 1 to 10 and Comparative Examples 1 to 15 were tested, and the test results are shown in Table 4 below.

[0090] 1. High temperature storage test of lithium-ion batteries: Place the lithium-ion batteries in a 25℃ constant temperature chamber and let them stand for 30 minutes to allow the lithium-ion batteries to reach a constant temperature. Charge the lithium-ion batteries that have reached a constant temperature at a constant current of 0.5C to a voltage of 4.48V, then charge at a constant voltage of 4.48V to a current of 0.05C, then discharge at a constant current of 0.2C to a voltage of 3.0V, record the initial capacity C1, then charge at a constant voltage of 4.48V to a current of 0.05C, and record the battery thickness T1. Transfer the battery to an 85℃ incubator and let it stand for 24h. After the battery is taken out and cooled, test the battery thickness T2. Discharge at a constant current of 0.2C to a voltage of 3.0V, record the remaining capacity C2, charge at a constant current of 0.5C to a voltage of 4.48V, then charge at a constant voltage of 4.4V to a current of 0.05C, then discharge at a constant current of 0.2C to a voltage of 3.0V, and record the recovery capacity C3.

[0091] 2. Lithium deposition test: Charge the lithium-ion battery to 4.48V at XXC constant current, then charge at constant voltage to 0.05C until fully charged, then discharge at 0.7C constant current to 3.0V, this is one charge and discharge cycle. Repeat the charge and discharge for 20 cycles, charge at XXC constant current to 4.48V, then charge at constant voltage to 0.05C until fully charged, transfer the battery to the glove box for disassembly, separate the negative electrode sheet, and observe whether there is lithium dendrite formation on its surface.

[0092] Table 4

[0093]

[0094]

[0095] From the test results in Table 4, it can be seen that Examples 1 to 10 can improve the expansion rate of the battery at high temperature and improve the safety performance of the battery compared to Comparative Example 1. This is due to the addition of a suitable proportion of dinitriles and polynitriles to the electrolyte. In addition, the electrolyte is complexed with the transition metal ions in the positive electrode material in the positive electrode sheet to improve the space utilization and the charge and discharge performance at high temperature.

[0096] From the test results in Comparative Examples 2-9, it can be seen that the charging capacity and high-temperature storage effect of adding a nitrile are not as good as the combined use of multiple nitriles. The combined use of multiple nitriles in proportion within the range can improve the charging capacity of the battery; from Table 4 above, it can be seen that if the nitrile addition ratio is not met and the mass content of a single nitrile is too high, the charging capacity and storage effect of the battery are worse than those in the embodiment. From Comparative Examples 10-15, it can be seen that different pole pieces also affect the charging capacity of the battery. Pole piece D has the best effect and can effectively reduce the risk of lithium precipitation.

[0097] In summary, the present invention has significant advantages in improving high-temperature storage and charging efficiency by adjusting the electrolyte components and using the positive electrode sheet of the present invention. The positive electrode material used can effectively improve the interface stability of the positive electrode material, and the added nitrile compound can effectively complex the transition metal ions on the positive electrode surface, thereby further reducing the side reactions of the positive electrode and the electrolyte, and improving the stability and safety performance of the battery under high-temperature storage.

[0098] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A lithium ion battery, comprising a positive electrode and an electrolyte, characterized in that: The positive electrode material of the positive electrode sheet includes a core body and a surface layer located on the surface of the core body; wherein the core body includes a chemical formula of Li a MO b The main material is a, a has a value range of 1 to 3, b has a value range of 1 to 3, M is at least one of transition metal ions, and the valence state of the M ion is +X; the surface layer contains A ions, and the valence state of the A ions is +Y; the core contains B ions, and the valence state of the B ions is +Z; wherein both A and B are at least one of the main group or subgroup elements of IA to IVA; and X, Y, and Z satisfy the relationship: 1<Z<X≤Y; The electrolyte includes dinitrile compounds and polynitrile compounds, the dinitrile compounds are two or more, and the content of each of the dinitrile compounds does not exceed 2% of the total mass of the electrolyte, the number of nitrile groups in the polynitrile compounds is ≥3, the polynitrile compounds are at least one, and the content of each of the polynitrile compounds does not exceed 3% of the total mass of the electrolyte; the total content of the dinitrile compounds is E%, and the total content of the polynitrile compounds is F%, wherein F≤E≤3F.

2. The lithium-ion battery according to claim 1, characterized in that The dinitrile compound includes at least two of succinonitrile, adiponitrile, glutaronitrile, 2-methyleneglutaronitrile, pimelonitrile, suberonitrile, and 2-fluoroadiponitrile; the polynitrile compound includes at least one of 1,2,3-tris(2-cyanoxy)propane, 1,3,6-hexanetricarboxylic acid nitrile, 1,3,5-pentanetricarboxylic acid nitrile, 1,2,2,3-tetracyanopropane, and 1,2,4,5-tetracyanobenzene.

3. The lithium-ion battery according to claim 1, characterized in that Based on the mass of the main material, the mass content of the M ions is ≥10%.

4. The lithium-ion battery according to claim 1, characterized in that: The weight proportion of the A ions in the surface layer is ≥200ppm; and / or, the interval extending 1μm from the surface of the core body toward its center is defined as the inner layer, and the weight proportion of the B ions in the inner layer is ≥200ppm.

5. The lithium-ion battery according to claim 1, characterized in that: The weight proportion of B ions in the surface layer is 0 to 100 ppm; and / or the weight proportion of A ions in the inner layer is 0 to 100 ppm.

6. The lithium ion battery according to any one of claims 1 to 5, characterized in that: The method for preparing the positive electrode active material comprises the following steps: S1, mixing the main material preparation raw materials including the lithium source and the M element precursor, then dispersing them in an organic solvent, adding the B element precursor for premixing, and vacuum drying the mixture; S2, dividing the mixture in step S1 into two groups, a and b, and then sintering them respectively to obtain product a and product b; S3, crushing the product a and the product b prepared in S2 respectively to obtain large particles of product a and small particles of product b; S4, mixing the large particles and small particles obtained in S3 in a mass ratio of (7-9):(1-3), adding the A element precursor, and stirring and mixing; S5. The mixture obtained in S4 is subjected to secondary sintering, crushing, and cooling to obtain the positive electrode material.

7. The lithium-ion battery according to claim 6, characterized in that: In step S1, the premixing speed is 200-400 r / min, and the premixing time is 4-8 hours; the vacuum drying temperature is 60-100° C., and the drying time is 10-15 hours.

8. The lithium-ion battery according to claim 6, characterized in that In step S2, the primary sintering temperature is 800-1200°C, the primary sintering of the mixture of group a adopts a two-stage sintering method and the sintering time is 12-14 hours, and the primary sintering time of the mixture of group b is 5.5-7.5 hours; Preferably, the two-stage sintering method includes: first continuously heating the temperature to D1°C at a heating rate of V1°C / min, then sintering at D1°C±50°C for t1 time, then continuously heating the temperature to D2°C at a heating rate of V2°C / min, then sintering at D2°C±50°C for t2 time, and finally annealing at a cooling rate of V3°C / min, wherein V1>V2, V2=V3, D1<D2, and t1=t2.

9. The lithium-ion battery according to claim 6, characterized in that: In step S3, the crushed product a is large particles of 5 to 50 μm, and the crushed product b is small particles of 0.5 to 10 μm.

10. The lithium ion battery according to claim 6, characterized in that: In step S5, the secondary sintering temperature is 600-800° C., and the sintering time is 8-12 hours.